Halotolerant Rhizobacteria Promote Growth and Enhance Salinity Tolerance in Peanut - Sharma, Sandeep; Kulkarni, Jayant; Jha, Bhavanath (Frontiers in Microbiology, 2016)
Use of Plant growth promoting rhizobacteria (PGPR) is a promising strategy to improve the crop production under optimal or sub-optimal conditions. In the present study, five diazotrophic salt tolerant bacteria were isolated from the roots of a halophyte, Arthrocnemum indicum. The isolates were partially characterized in vitro for plant growth promoting traits and evaluated for their potential to promote growth and enhanced salt tolerance in peanut. The 16S rRNA gene sequence homology indicated that these bacterial isolates belong to the genera, Klebisiella, Pseudomonas, Agrobacterium and Ochrobactrum. All isolates were nifH positive and able to produce indole -3-acetic acid (ranging from 11.5 to 19.1 µg ml-1). The isolates showed phosphate solubilisation activity (ranging from 1.4 to 55.6 µg phosphate /mg dry weight), 1-aminocyclopropane-1-carboxylate deaminase activity (0.1 to 0.31 µmol α-kB/µg protein/h) and were capable of reducing acetylene in acetylene reduction assay (ranging from 0.95 to 1.8 µmol C2H4 mg protein/h). These isolates successfully colonized the peanut roots and were capable of promoting the growth under non-stress condition. A significant increase in total nitrogen (N) content (up to 76%) was observed over the non-inoculated control. All isolates showed tolerance to NaCl ranging from 4-8% in nutrient broth medium. Under salt stress, inoculated peanut seedlings maintained ion homeostasis, accumulated less reactive oxygen species (ROS) and showed enhanced growth compared to non-inoculated seedlings. Overall, the present study has characterized several potential bacterial strains that showed an enhanced growth promotion effect on peanut under control as well as saline conditions. The results show the possibility to reduce chemical fertilizer inputs and may promote the use of bio-inoculants.